Factors Associated with Foodborne Pathogens among Food Handlers: A Case Study of Thika, Kiambu County, Kenya - Joseph Maina Kimemia; John Gachuki Kariuki; Alfred Owino Odongo; Paul Ng’ang’a Murima (Advances in Public Health, 2023)
Increasing risks of infections with foodborne pathogens may occur as a result of poor food handling practices. The present cross-sectional study employed a mixed-methods approach to determine the factors associated with foodborne pathogens among food handlers working in the food establishments in Thika, Kiambu County, Kenya. Random sampling was used to enroll respondents in the survey. A single stool specimen was collected from each study participant. Laboratory analysis of the specimen was done to test the selected foodborne pathogens. Overall, 44 out of the 285 food handlers who took part in the study had at least one food-transmitted pathogen, putting the prevalence of foodborne infections among the food handlers at 15.4% (95% confidence interval (CI) 11.7%–20.1%). The findings from multivariate logistic regression indicated the following protective factors for foodborne pathogens among the studied food handlers: being female (adjusted odds ratio (AOR) 0.098 (95% CI 0.0304–0.315, p<0.001)); having a valid medical examination certificate (AOR 0.141 (95% CI 0.141–1. 0.439, p=0.001)); not boiling or treating water before serving the water to customers was a risk factor for having infections with foodborne pathogens (AOR 3.043 (95% CI 1.2225–7.577, p=0.017)). The presence of foodborne pathogens among the food handlers in the study area potentially highlights the need to address the spread and transmission of foodborne infections in the study area. There is a need to institute appropriate control measures, including regular screening of food handlers for foodborne illnesses in addition to training them on safe food handling practices, hand hygiene practices, and regular monitoring of the food handling practices.